Screening for Lynch Syndrome among Patients with Newly Diagnosed Endometrial Cancer: A Comprehensive Review. Issue 6 (November 2016) - Aguirre, Elena; Grana, Begoña; Boudet, Miguel; Balmana, Judith
Lynch syndrome (LS) is an autosomal dominant condition characterized by an increased risk of hereditary colorectal, endometrial, ovarian, pancreatic, urinary tract, and gastric cancer. It is estimated that around 5% of all endometrial cancer (EC) cases are due to an inherited predisposition, of which LS might be the most frequent. The lifetime risk of developing EC in women with LS ranges between 40% and 71% depending on the type of mutation. In many cases, this risk may even exceed their risk of developing colon cancer. Moreover, in 60% of these women, EC will be the first primary malignancy diagnosed and the sentinel diagnosis of the syndrome. Therefore, it is essential to identify which women with EC have LS in order to allow implementation of individualized screening and preventive strategies.